2002
DOI: 10.1007/s11769-002-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Snow cover monitoring by remote sensing and snowmelt runoff calculation in the upper Huanghe River basin

Abstract: The upper Huanghe(Yellow) River basin is situated in the northeast of the Qinghai-Xizang(Tibet)Plateau of China. The melt-water from the snow-cover is main water supply for the rivers in the region during springtime and other arid regions of the northwestern China, and the hydrological conditions of the rivers are directly controlled by the snowmeh water in spring. So snowmeh runoff forecast has importance for hydropower, flood prevention and water resources utilization. The application of remote sensing and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Number of researchers and indexes have been developed using remote sensing sensors and data, such as MODIS, Landsat TM, +ETM, OLI/TIRS etc. Normalized Difference Snow Index has been widely used in snow monitoring [4][5][6], as well as other indexes and ratios [7][8][9]. The NDSI in some cases is identical as the Normalized Difference Water Index NDWI [10] values.…”
Section: Introductionmentioning
confidence: 99%
“…Number of researchers and indexes have been developed using remote sensing sensors and data, such as MODIS, Landsat TM, +ETM, OLI/TIRS etc. Normalized Difference Snow Index has been widely used in snow monitoring [4][5][6], as well as other indexes and ratios [7][8][9]. The NDSI in some cases is identical as the Normalized Difference Water Index NDWI [10] values.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, optical remote sensing data (e.g., AVHRR and Terra/MODIS) have been used to monitor snow properties in Xinjiang [10,11]. Compared with in situ observations over four winters in northern Xinjiang, results showed that MODIS data are preferable to AVHRR data for snow monitoring in Xinjiang [12,13]. However, there are very few studies of seasonal snow cover monitoring in northeastern China [14,15].…”
Section: Introductionmentioning
confidence: 99%